2012
DOI: 10.1111/apha.12040
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress activates the Akt/mTOR signalling pathway in rat skeletal muscle

Abstract: Our data indicate that the altered temperature increased phosphorylation in a temperature-dependent manner in rat skeletal muscle and may itself be a key stimulator of Akt/mTOR signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 53 publications
6
77
4
1
Order By: Relevance
“…In contrast to our findings, a previous study reported that HS for 30 min activated p70S6K in rat skeletal muscle in vivo 10) . These contrasting results may be attributed to differences in the heat exposure process.…”
Section: Fig 2 Changes In Buffer Ph During Incubationcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, a previous study reported that HS for 30 min activated p70S6K in rat skeletal muscle in vivo 10) . These contrasting results may be attributed to differences in the heat exposure process.…”
Section: Fig 2 Changes In Buffer Ph During Incubationcontrasting
confidence: 99%
“…4E-BP1 phosphorylation and protein synthesis are suppressed during resistance-or endurancetype exercise 1,2) , which may be attributed to the negative regulation of mTOR by AMPK 9) . In contrast, it has been shown that HS activates the mTOR pathway in skeletal muscle 10) and thereby contributes the prevention of skeletal muscle atrophy 11) . However, the direct effect of shortterm HS on protein synthesis in skeletal muscle remains unclear.…”
Section: Introductionmentioning
confidence: 94%
“…5). We and others have reported increased circulating insulin concentrations [15], [16] and signaling [17] in response to acute postnatal HS in a variety of models. While the reason for enhanced circulating insulin during HS response remains unclear, it likely includes insulin's role in activating the cellular stress response [48].…”
Section: Discussionmentioning
confidence: 72%
“…Although the mechanisms responsible for HS induced alterations in body composition are not completely understood, it may be partially explained by our recent finding that basal insulin increased in a variety of HS models [15] including pigs [16]. Additionally, it was recently reported in a rodent model that HS stimulates insulin signaling in skeletal muscle [17]. The increase in insulin (a potent anabolic signal) occurs despite the marked reduction in feed intake and hyper-catabolic hormonal milieu that dominates during HS [1], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heat stress affects protein anabolism and catabolism as well as satellite cell proliferation, all of which play important roles in determining muscle growth and development4. In addition, heat stress activates signaling pathways associated with the regulation of skeletal muscle growth and development56.…”
mentioning
confidence: 99%